PERILAKU PENDERITA TB PARU POSITIF DALAM UPAYA PENCEGAHAN PENULARAN TUBERKULOSIS PADA KELUARGA DI KECAMATAN PANDAN KABUPATEN TAPANULI TENGAH TAHUN 2012 - sedar malem; Eddy Syahrial; Syarifah harahap (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
Abstract Tuberculosis (TB) is an infectious disease directly caused by the bacteria Mycobacterium tuberculosis. Germs will grow optimally at temperatures around 37 ° C according to the normal temperature of the human body, tuberculosis bacilli survive for months at room temperature and in a dark and damp, and die quickly in direct sunlight. This study aims to describe the behavior of patients with positive pulmonary TB in preventing transmission of TB to families in District Pandan Central Tapanuli 2012. Type of study design is a descriptive survey method. The study population was all patients with positive pulmonary TB in Pandan districts and as many as 138 people sampled 58 respondents drawn by simple random sampling. Data were obtained through interviews using a questionnaire and analyzed by univariate, presented in frequency distribution. Research results showed that based on the characteristics of the respondents obtained most aged> 30 years 40 people (69.0%), male Sex in 38 people (69.0%), level of education high school 30 people (51.7%), not worked a total of 35 people (60.3%). Knowledge of respondents in the category of either the 36 people (62.1%), attitude of the respondents in both categories is 54 people (93.1%). Measures most respondents in this category is less than 56 people (96.6%). Expected for health workers to provide health services effectively and efficiently, the importance of prevention of Tuberculosis information on the family